INDONESIA’S COMMERCIAL DIPLOMACY STRATEGY IMPLEMENTED BY THE INDONESIAN EMBASSY IN TOKYO (KBRI TOKYO) IN JAPAN, 2020–2023 - Mutiara Azzahra Dwi Putri; Sonny Sudiar (Regionalism Global Journal: Jurnal Hubungan Internasional, 2026)
The COVID-19 pandemic since 2020 disrupted global economic activities, including trade relations between Indonesia and Japan. In 2023, Indonesia recorded a significant recovery, with export volume growth exceeding 5%, reflecting the success of national strategies supported by commercial diplomacy. Japan, as a key strategic partner in East Asia, contributed through cooperation in trade, investment, and the creative industries. This study, entitled “Indonesia’s Commercial Diplomacy Strategy by the Embassy of the Republic of Indonesia (KBRI) in Tokyo, 2020–2023”, examines the strategies and implementation of commercial diplomacy conducted by KBRI Tokyo to advance Indonesia’s economic interests during the pandemic and post-pandemic period. The research employs a qualitative descriptive-analytical approach with illustrative methods, focusing on activities such as export promotion, trade fairs, and business matching facilitation. The findings indicate that KBRI Tokyo adopted adaptive strategies by optimizing digital promotion and strengthening sustainable investment cooperation, despite challenges related to product standards and regulatory barriers.